2016
DOI: 10.1097/01.ogx.0000499796.07733.a1
|View full text |Cite
|
Sign up to set email alerts
|

Single Deepest Vertical Pocket or Amniotic Fluid Index as Evaluation Test for Predicting Adverse Pregnancy Outcome (SAFE Trial): A Multicenter, Open-Label, Randomized Controlled Trial

Abstract: (Abstracted from Ultrasound Obstet Gynecol 2016;47:674–679) One of the important aspects of fetal well-being assessment is amniotic fluid volume, lack of which leads to oligohydramnios and consequently adverse perinatal outcomes. Amniotic fluid estimation by ultrasound can be performed by assessment of the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
3
11
1
1
Order By: Relevance
“…A systematic review of randomized trials determined that MVP should be the method of choice, since the use of AFI increases the rate of diagnosis of oligohydramnios, induction of labor and Cesarean delivery without improving pregnancy outcome 35 . A subsequent trial confirmed these findings 36 . Our study is the first to assess the interobserver variability of AFI and MVP measurements according to BMI.…”
Section: Discussionmentioning
confidence: 72%
“…A systematic review of randomized trials determined that MVP should be the method of choice, since the use of AFI increases the rate of diagnosis of oligohydramnios, induction of labor and Cesarean delivery without improving pregnancy outcome 35 . A subsequent trial confirmed these findings 36 . Our study is the first to assess the interobserver variability of AFI and MVP measurements according to BMI.…”
Section: Discussionmentioning
confidence: 72%
“…Both AFI and DVP correlate poorly with the actual dye-calculated volume of amniotic fluid, and neither of them appears significantly better than the other 37 . However, it appears that AFI identifies more women as having oligohydramnios than does DVP, thereby increasing the rate of labor induction, but without improving the clinical outcome 37,38 . Observational evidence comparing ultrasound with dye-determination of amniotic fluid volume has shown that DVP may be superior for identifying oligohydramnios and the AFI superior for identifying polyhydramnios 39 .…”
Section: Recommendationmentioning
confidence: 99%
“…In light of the technical advances in the field of fetal monitoring, the routine examination methods currently used at term and the "classic" PD markers such as amniotic fluid volume, estimated fetal weight (EFW) and fetal heart rate patterns (FHR) may be insufficient to adequately assess placental function. While an oligohydramnios (single deepest pocket < 2 cm [6]), a low estimated fetal weight (EFW) and an abdominal circumference (AC) between the 3rd and 10th percentile (SGA: small for gestational age [7]) or below the 3rd percentile (FGR: fetal growth restriction [7]), as well as pathological changes of the fetal heart rate patterns (according to FIGO [8,9]) are all pivotal for the diagnosis of a PD, the concentration on solely these parameters bears the risk of overlooking an inapparent PD which may potentially effect perinatal outcome. In addition to this, there are theoretical limitations in the pathophysiological climax of the PD (oligohydramniosdue to insufficient fetal renal circulationas a typical late sign of PD) [10,11], technical limitations due to the limited reproducibility and predictive power of cardiotocography (CTG) [8, 12 -14] as well aswith regard to the EFWa reinterpretation of FGR independent of cutoff values (meaning, a FGR and thus, a PD may also occur at an EFW > 10th percentile) [7] and the "ideal" birth weight percentile [15].…”
Section: Induction Of Labormentioning
confidence: 99%
“…Angesichts des technischen Fortschritts im Bereich der fetalen Überwachung sind die bislang routinemäßig eingesetzten Untersuchungstechniken und "klassischen" Marker der PD wie die Fruchtwassermenge, das fetale Schätzgewicht (SG) und das fetale Herzfrequenzmuster (FHF) am Termin womöglich unzureichend, wenn es um die adäquate Beurteilung der Plazentafunktion geht. Zwar sind Oligohydramnion (single deepest pocket < 2 cm [6]), niedriges Schätzgewicht (SG) bzw. Abdomenumfang (AU) im Bereich der 3.-10.…”
Section: Introductionunclassified